2020
DOI: 10.1111/irv.12771
|View full text |Cite
|
Sign up to set email alerts
|

Results from the WHO external quality assessment for the respiratory syncytial virus pilot, 2016‐17

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We should learn from past failures like the suptavumab trial 11 . Current programs include the WHO Global RSV Surveillance program 34 (Mozambique, Sierra Leone, South Africa, Argentina, Brazil, Canada, Chile, Egypt, Russia, the UK, India, Thailand, Australia, Mongolia) and the OUTSMART program (the USA) 35 . We demonstrated that almost all global RSV B strains collected between 2015 and 2018 reported amino acid mutations in the suptavumab target epitope sequence.…”
Section: Discussionmentioning
confidence: 94%
“…We should learn from past failures like the suptavumab trial 11 . Current programs include the WHO Global RSV Surveillance program 34 (Mozambique, Sierra Leone, South Africa, Argentina, Brazil, Canada, Chile, Egypt, Russia, the UK, India, Thailand, Australia, Mongolia) and the OUTSMART program (the USA) 35 . We demonstrated that almost all global RSV B strains collected between 2015 and 2018 reported amino acid mutations in the suptavumab target epitope sequence.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, mAbs can show sustained efficacy during long-term clinical use, provided they are specific for a stable epitope of RSV (nirsevimab binding epitopes: amino acids 62–69, 196–212). Nevertheless, ongoing molecular surveillance of RSV globally is key, with current initiatives including the WHO Global RSV Surveillance program, the OUTSMART, and INFORM programs ( Figure 2 ) ( 123 125 ).…”
Section: Considerations Of the Different Strategies For Protecting Al...mentioning
confidence: 99%
“…One of the aims of the initial phase of the global surveillance was to evaluate and standardise WHO recommended and other existing RSV molecular tests to enable the accurate detection of RSV by laboratories in all six WHO regions. To achieve this, in 2016, the first External Quality Assessment exercise for the molecular detection of RSV was successfully developed, launched, and completed by the 14 participating national laboratories 4 . Following the successful implementation of Phase I in 2018, this was expanded to 26 countries in Phase II, each with a national laboratory participating in the Global RSV surveillance Program (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, in 2016, the first External Quality Assessment exercise for the molecular detection of RSV was successfully developed, launched, and completed by the 14 participating national laboratories. 4 Following the successful implementation of Phase I in 2018, this was expanded to 26 countries in Phase II, each with a national laboratory participating in the Global RSV surveillance Program (Table S1 ). This study describes the second of the WHO External Quality Assessments (EQA) performed during 2019–2020 for the molecular detection of RSV.…”
Section: Introductionmentioning
confidence: 99%